The analysis of the pulmonary domain involvement in Sjögren’s disease - Marta Madej; Krzysztof Proc; Piotr Wawryka; Ewa Morgiel; Maciej Sebastian; Piotr Wiland; Agata Sebastian (Therapeutic Advances in Musculoskeletal Disease)
Background: The EULAR Sjögren’s syndrome (SS) disease activity index (ESSDAI) pulmonary domain is used to assess the activity of respiratory system involvement in Sjögren’s disease (SjD). The most unfavorable form of respiratory involvement in SjD, after lymphomas, is interstitial lung disease (ILD). Objectives: The aim of the study was to assess the involvement of the respiratory system in SjD patients and the occurrence of ILD in high-resolution computed tomography (HRCT), depending on immunological markers, the influence of cigarette smoking, and the age of the patients. Design: Single-center, registry, cohort study. Methods: Among all SjD patients, a group with involvement in the pulmonary domain was distinguished. This group was later subjected to a detailed analysis of immunological and serological markers and chest imaging tests. Results: In all, 64 patients out of 299 with SjD had involvement in the pulmonary domain defined according to the ESSDAI definition. The most frequently reported clinical symptoms of respiratory system involvement included dryness and chronic cough (over 80% of patients), followed by shortness of breath. Nine percent of patients with changes in lungs were asymptomatic. Patients with pulmonary involvement were older (54 vs 48 years, p  < 0.05). In the subpopulation of patients with SjD and pulmonary involvement, the presence of rheumatoid factor (73% vs 60%, p  < 0.05), and hematological domain involvement according to ESSDAI (54% vs 37%, p  < 0.05) were more common. In the group of 64 patients with a positive pulmonary domain, 34 (53%) had ILD on HRCT. A higher incidence of comorbidities was found in the population of patients with ILD. No correlation was found between the type of lung involvement and the immunological profile, inflammatory markers, age, and smoking habit. Conclusion: Involvement of the pulmonary domain is common in patients with SjD. However, the clinical picture is very heterogeneous, which determines the subsequent personalization of treatment.